The causal effect of education on health behaviors: Evidence from Turkey - Aysit Tansel; Hanife Deniz Karaoğlan (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
This study provides causal effect of education on health behaviors in Turkey which is a middle income developing country. Health Survey of the Turkish Statistical Institute for the years 2008, 2010 and 2012 are used. The health behaviors considered are smoking, alcohol consumption, fruit and vegetable consumption, exercising and one health outcome namely, the body mass index (BMI). We examine the causal effect of education on these health behaviors and the BMI Instrumental variable approach is used in order to address the endogeneity of education to health behaviors. Educational expansion of the early 1960s is used as the source of exogenous variation in years of schooling. Our main findings are as follows. Education does not significantly affect the probability of smoking or exercising. The higher the education level the higher the probability of alcohol consumption and the probability of fruit and vegetable consumption. Higher levels of education lead to higher BMI levels. This study provides a baseline for further research on the various aspects of health behaviors in Turkey.
Keywords: I10; I12; I19; 330; Turkey; Health Behaviors; Education; Instrumental Variable Estimation